PENGARUH SISTEM TANAM DAN PEMBERIAN PUPUK ORGANIK LIMBAH SAGU TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PADI (Oryza Sativa L.) KULTIVAR MEKONGGA - Geissler Wally (Agrotek, 2022)
The program to increase food security is the government's main target in meeting the needs of the Indonesian people. Several programs have been carried out to achieve food security, including improving irrigation networks, optimizing land, and intensifying agriculture. Rice is a national food ingredient that is the main target, because it is still a staple food for almost all Indonesian people. Sorong Regency is part of West Papua Province which has relatively wide land potential for the development of agricultural commodities. This study aims to determine the cropping system and the effect of sago waste that is able to provide the highest productivity of the Mekongga cultivar rice plant in Sorong Regency. The research was conducted at the Experimental Ground of the Agrotechnology Study Program, Faculty of Engineering and Agriculture, Nani Bili Nusantara University, Sorong Regency. The research was carried out from July to November 2021. The research method used was an experimental method and the experimental design used was a single factor randomized block design, with nine treatments repeated three times. There are nine combinations of treatment systems for planting and giving sago waste. The results showed that the cropping system and the application of sago waste for rice (Oryza Sativa L.) cultivar Mekongga had a significant effect on plant heights of 42, 56, and 70 days after planting. The number of tillers at the age of 42, 56, and 70 DAP, the number of panicles per clump, the number of grains per panicle, the Legowo 4:1 planting system and with 300 grams of sago waste gave the highest number of grains per panicle.